Respostas

  • Usuário do Brainly
2014-09-02T21:38:25-03:00
a-b=\dfrac{9}{20}

a=b+\dfrac{9}{20}

ab=1

\left(b+\dfrac{9}{20}\right)b=1

b^2+\dfrac{9b}{20}=1

20b^2+9b-20=0

\Delta=9^2-4\cdot20\cdot(-20)=81+1~600~=1~681

b=\dfrac{-9\pm\sqrt{1~681}}{2\cdot20}=\dfrac{-9\pm41}{40}

b'=\dfrac{-9+41}{40}=\dfrac{32}{40}=\dfrac{4}{5}

a'=\dfrac{4}{5}+\dfrac{9}{20}=\dfrac{16+9}{20}=\dfrac{25}{20}=\dfrac{5}{4}.

b"=\dfrac{-9-41}{40}=\dfrac{-50}{40}=\dfrac{-5}{4}

a"=\dfrac{4}{5}+\left(\dfrac{-5}{4}\right)=\dfrac{16-20}{20}=\dfrac{-4}{5}

(a,b)=(\frac{5}{4},\frac{4}{5})

(a,b)=(\frac{-4}{5},\frac{-5}{4})
Muito obrigado!! melhor resposta que já vi até hoje, haha
De nada, obgd c: